Executive compensation and corporate performance in China's real estate industry - Zhang, Mengyu (2020)
By analyzing the relevant data of China's listed real estate companies from 2015 to 2019, I find that executive compensation has been increasing year by year. In 2019, the compensation of executives of listed real estate companies had nearly doubled. However, corporate performance showed a trend of fluctuating growth. Based on this, this article studies the correlation between executive compensation of listed real estate companies and corporate performance. This article expounds on the principal-agent theory, human capital theory, and efficiency wage theory. In the empirical analysis, this paper adopts the panel data analysis method for analysis. The research results show that executive compensation has a significant positive impact on corporate performance in the real estate industry. To a certain extent, it shows that implementing the annual salary system in which performance and salary are linked in China has played a better supervision and incentive role. At the same time, the corporate performance also has a significant positive impact on executive compensation. This shows that executive compensation of listed real estate companies in China is based on corporate performance. The improvement of corporate performance has promoted an increase in executive compensation. I also find that executive compensation is positively correlated with the company's size, that is, the larger the company is, the higher the executive compensation is. Also, I find that executive compensation is negatively correlated with the largest shareholder's concentration of ownership.